Pengaruh Pemahaman Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak UMKM di Bandung - Dedeh Faridah; Sopian, Sopian; Aditya Santoso (BADAN PENERBIT STIEPARI PRESS, 2025)
One of the main sources of state funding for government and national development is tax revenue. About 61% of the national GDP comes from MSMEs. The fact that the percentage of formal compliance of MSME taxpayers is still below 65% indicates that there are still problems in implementing tax policies. The purpose of this study was to determine the effect of tax understanding and tax sanctions on MSME taxpayer compliance. This study uses quantitative research with data collection techniques using questionnaires and Likert scales. The population in this study were MSME taxpayers in Bandung Regency, with sampling using the slovin formula, so that the sample obtained was 100 MSME taxpayers. The data analysis technique used is multiple linear regression with the SPSS version 25 program. The results showed that tax understanding and tax sanctions have a positive influence on taxpayer compliance both partially and simultaneously.